Targeted Treatment of Individuals With Psychosis Carrying a Copy Number Variant Containing a Genomic Triplication of the Glycine Decarboxylase Gene. - Bodkin, J Alexander; Coleman, Michael J; Godfrey, Laura J; Carvalho, Claudia M B; Morgan, Charity J; Suckow, Raymond F; Anderson, Thea; Öngür, Dost; Kaufman, Marc J; Lewandowski, Kathryn E; Siegel, Arthur J; Waldstreicher, Elliot; et al. (Biol Psychiatry, 2019)
BACKGROUND: The increased mutational burden for rare structural genomic variants in schizophrenia and other neurodevelopmental disorders has so far not yielded therapies targeting the biological effects of specific mutations. We identified two carriers (mother and son) of a triplication of the gene encoding glycine decarboxylase, GLDC, presumably resulting in reduced availability of the N-methyl-D-aspartate receptor coagonists glycine and D-serine and N-methyl-D-aspartate receptor hypofunction. Both carriers had a diagnosis of a psychotic disorder. METHODS: We carried out two double-blind, placebo-controlled clinical trials of N-methyl-D-aspartate receptor augmentation of psychotropic drug treatment in these two individuals. Glycine was used in the first clinical trial, and D-cycloserine was used in the second one. RESULTS: Glycine or D-cycloserine augmentation of psychotropic drug treatment each improved psychotic and mood symptoms in placebo-controlled trials. CONCLUSIONS: These results provide two independent proof-of-principle demonstrations of symptom relief by targeting a specific genotype and explicitly link an individual mutation to the pathophysiology of psychosis and treatment response.

Marker chromosome genomic structure and temporal origin implicate a chromoanasynthesis event in a family with pleiotropic psychiatric phenotypes. - Grochowski, Christopher M; Gu, Shen; Yuan, Bo; Tcw, Julia; Brennand, Kristen J; Sebat, Jonathan; Malhotra, Dheeraj; McCarthy, Shane; Rudolph, Uwe; Lindstrand, Anna; Chong, Zechen; Levy, Deborah L; et al. (Hum Mutat, 2018)
Small supernumerary marker chromosomes (sSMC) are chromosomal fragments difficult to characterize genomically. Here, we detail a proband with schizoaffective disorder and a mother with bipolar disorder with psychotic features who present with a marker chromosome that segregates with disease. We explored the architecture of this marker and investigated its temporal origin. Array comparative genomic hybridization (aCGH) analysis revealed three duplications and three triplications that spanned the short arm of chromosome 9, suggestive of a chromoanasynthesis-like event. Segregation of marker genotypes, phased using sSMC mosaicism in the mother, provided evidence that it was generated during a germline-level event in the proband's maternal grandmother. Whole-genome sequencing (WGS) was performed to resolve the structure and junctions of the chromosomal fragments, revealing further complexities. While structural variations have been previously associated with neuropsychiatric disorders and marker chromosomes, here we detail the precise architecture, human life-cycle genesis, and propose a DNA replicative/repair mechanism underlying formation.